Utilization of microsatellites for the analysis of genomic alterations in colorectal cancers in Brazil - Fuzikawa,A.K. (1997)
Two different pathogenetic mechanisms are proposed for colorectal cancers. One, the so-called "classic pathway", is the most common and depends on multiple additive mutational events (germline and/or somatic) in tumor suppressor genes and oncogenes, frequently involving chromosomal deletions in key genomic regions. Methodologically this pathway is recognizable by the phenomenon of loss of heterozygosity. On the other hand, the "mutator pathway" depends on early mutational loss of the mismatch repair system (germline and/or somatic) leading to accelerated accumulation of gene mutations in critical target genes and progression to malignancy. Methodologically this second pathway is recognizable by the phenomenon of microsatellite instability. The distinction between these pathways seems to be more than academic since there is evidence that the tumors emerging from the mutator pathway have a better prognosis. We report here a very simple methodology based on a set of tri-, tetra- and pentanucleotide repeat microsatellites allowing the simultaneous study of microsatellite instability and loss of heterozygosity which could allocate 70% of the colorectal tumors to the classic or the mutator pathway. The ease of execution of the methodology makes it suitable for routine clinical typing